PENGARUH VARIASI PRODUK, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOPI KULO GALUH MAS KARAWANG - Andre Baskara; Netti Nurlenawati; Dexi Triadinda (Institut Teknologi dan Bisnis Dewantara, 2023)
This study is to determine the influence of product variations and promotions on purchases at Kopi Kulo Galuh Mas Karawang. This type of research is kuantitative research. The population of this study were consumers who had already shopped and would shop at Kopi Kulo and the number of samples to be studied was 96 respondents. The sampling technique uses the lemeshow sample. In obtaining data and information that will support this research, the authors collect data by means of observations, questionnaires, literature studies. The results of the study obtained that product variations have a positive and significant effect partially on purchasing decisions at Kopi Kulo Galuh Mas Karawang, Promotions have a partial positive effect on purchasing decisions at Kopi Kulo Galuh Mas Karawang, and Product variations and promotions have a positive and significant effect simultaneously on purchasing decisions at Kopi Kulo Galuh Mas Karawang.